Bioactive compounds from nature: Antioxidants targeting cellular transformation in response to epigenetic perturbations induced by oxidative stress - Bouyahya, Abdelhakim; Bakrim, Saad; Aboulaghras, Sara; El Kadri, Kawtar; Aanniz, Tarik; Khalid, Asaad; Abdalla, Ashraf N.; Abdallah, Ahmed A; Ardianto, Chrismawan; Long, Chiau Ming *; El Omari, Nasreddine (Elsevier, 2024)
Oxidative stress results from a persistent imbalance in oxidation levels that promotes oxidants, playing a crucial role in the early and sustained phases of DNA damage and genomic and epigenetic instability, both of which are intricately linked to the development of tumors. The molecular pathways contributing to carcinogenesis in this context, particularly those related to double-strand and single-strand breaks in DNA, serve as indicators of DNA damage due to oxidation in cancer cases, as well as factors contributing to epigenetic instability through ectopic expressions. Oxidative stress has been considered a therapeutic target for many years, and an increasing number of studies have highlighted the promising effectiveness of natural products in cancer treatment. In this regard, we present significant research on the therapeutic targeting of oxidative stress using natural molecules and underscore the essential role of oxidative stress in cancer. The consequences of stress, especially epigenetic instability, also offer significant therapeutic prospects. In this context, the use of natural epi-drugs capable of modulating and reorganizing the epigenetic network is beginning to emerge remarkably. In this review, we emphasize the close connections between oxidative stress, epigenetic instability, and tumor transformation, while highlighting the role of natural substances as antioxidants and epi-drugs in the anti-tumoral context.